Satisfaction and meaning in life for persons with traumatic spinal cord injury - Castro, Fabiana Faleiros Santana; Bimbatti, Karina de Fátima; Carvalho, Adriane Aparecida Gonçalves de; Gonçalves, Mariele Lenhari; Lopes, Filipe Gustavo; Schutt, William (Acta Fisiátrica, 2020)
Objective: To analyze meaning in life, satisfaction with life, and the influence of sociodemographic variables in Brazilians with Spinal Cord Injury (SCI). This was a quantitative, cross-sectional, and descriptive study. Participants: Adults with traumatic SCI. Methods: The data were collected through the Survey Monkey platform using the Meaning in Life Questionnaire and the Satisfaction With Life Scale; the sample was composed of adults 18 years old or older with Traumatic SCI. Results: Most of the participants were male (75.5%), with a mean age of 36.22. The average score on the Satisfaction With Life Scale was 21.26, which corresponds to the Slightly satisfied category. The mean scores, respectively, for search and presence of meaning in life were 22.61 and 25.32, indicating that most participants find life meaningful even though they don’t explicitly search for meaning. There were significant associations between satisfaction with life and the meaning in life. Conclusion: In the rehabilitation process for people with Traumatic SCI, the assessment of satisfaction and the meaning of life must be managed together along with other psychological variables. Considering the complex life context of people suffering from a Traumatic SCI, there is a need for both holistic and individualized understanding during the rehabilitation process.